Effect of Early Everolimus-Facilitated Reduction of Tacrolimus on Efficacy and Renal Function in De Novo Liver Transplant Recipients: 24-Month Results for the North American Subpopulation. Issue 2 (February 2017) - Chapman, William C.; Brown, Robert S.; Chavin, Kenneth D.; Sudan, Debra; Koneru, Baburao; Junge, Guido; Dong, Gaohong; Patel, Dharmesh; Teperman, Lewis; Fung, John J.
Abstract : Background: A recent randomized phase III study of 719 de novo liver transplant recipients showed that early everolimus plus reduced-dose tacrolimus (EVR + rTAC) led to significantly better kidney function than standard TAC (TAC-C), without compromising efficacy. In that study, patients from North America (n = 211) had increased risk factors for posttransplant renal insufficiency at study start, relative to patients from Europe and rest of world (eg, worse renal function, more diabetes, older age). Methods: A post hoc analysis was performed to assess whether these regional disparities affected study outcomes in North American patients. Results: In this subpopulation, estimated glomerular filtration rates at randomization were higher in TAC-C over EVR + rTAC (76.4 vs 69.3 mL/min per 1.73 m 2 ). Mean changes in estimated glomerular filtration rate values (mL/min per 1.73 m 2 ) favored EVR + rTAC over TAC-C at months 12 (+3.7 vs −4.5; P = 0.032), 24 (+2.7 vs −6.6; P = 0.042), and 36 (+4.3 vs −8.1; P = 0.059). The composite efficacy endpoint of treated biopsy-proven acute rejection, graft loss, or death was 10.9%, 14.1%, and 14.1% for EVR + rTAC and 13.1%, 17.2%, and 19.3% for TAC-C at months 12, 24, and 36, respectively. Conclusions: Although the North American cohort had more comorbidities, results were consistent with the overall population for efficacy and renal function. Abstract : In order to reduce nephrotoxicity in liver transplantation, several strategies are being explored including early everolimus-facilitated tacrolimus dose reduction, which in a recent multicenter study led to better kidney function versus standard TAC without compromising efficacy. In this North American cohort sub-analysis, results are similar despite higher baseline comorbidities.